Thermal behavior of pervious concrete in dry conditions. (22nd August 2022) - Seifeddine, Khaled; Amziane, Sofiane; Toussaint, Evelyne
Highlights: Thermal behavior of pervious concrete (PC) was assessed. An original experimental bench was designed to study the thermal behavior in the laboratory. The maximum surface temperature of PC is more sensitive to the albedo than to the thermal conductivity. To decrease the maximum temperature of PC, it is recommended to avoid the use of. Lightweight aggregates. It's recommended the use of finer and lighter colored aggregates (to increase the albedo). Abstract: As the world becomes more urbanized, concerns are growing about the phenomenon of urban heat islands (UHIs). In addition to the environmental function of stormwater management, pervious concrete (PC) pavements are also a solution that can help mitigate increasing urban temperatures, through cooling by evaporation. Several studies in the literature have focused on the evaporative cooling effect of PC, which requires the presence of water either from precipitation or irrigation. However, in countries that have dry summers and where watering techniques are complicated to implement, in hot weather and dry conditions, PC can have a higher temperature than traditional impermeable concrete. The main objective of this paper is therefore to study the influence of thermophysical parameters on the surface temperature of PC, with a view to designing a mix that minimizes its surface temperature in dry conditions. The thermal behavior of PC and ordinary impermeable concrete (OC) in dry condition have been studied both analytically and experimentally. All heat fluxes involved in the energy balance at the surface of both pavements were analyzed. The results show that PC has a surface temperature up to 6 °C higher than OC during the day and up to 4 °C lower during the night. Increasing the thermal conductivity of the pervious concrete makes the surface temperature of PC lower during the day but higher at night. On the other hand, increasing albedo makes the surface temperature of the pavement lower both during the day and during the night. Finally, the sensitivity study shows that the albedo has a greater influence on the maximum surface temperature of the PC than does thermal conductivity. To decrease the maximum temperature of PC, it is recommended to avoid the use of lightweight aggregates and to use finer and lighter colored aggregates (to increase the albedo), having high thermal conductivity. This mix optimization may be limited by the hydraulic properties of the PC due to its influence on the open porosity.